De niet-gelijkoorspronkelijkheid van ervaring en openbaring: Over Christus, kerk en sacramenten bij Edward Schillebeeckx - Geldhof, Joris (Tijdschrift voor theologie, 2007)
This article starts from the observation that there are striking differences in the way the earlier and later Schillebeeckx thought about the relation between Christ, church and sacraments. First the article explores and describes the difference between the two phases in the creation of Schillebeeckx’ sacramental theology. Then it seeks an explanation for the apparent disparities. It argues that a mere reference to the differences between the context in which theology was done fifty years ago and that in which it is done today is insufficient. It also takes into account that, unlike his treatment of the sacraments, Schillebeeckx’ study of experience and revelation as fundamental theological themes underwent no great development nor did it design divergent perspectives. On final analysis, he consistently defended the hermeneutical coincidence and theoretical inextricability of the two. However, Schillebeeckx also always recognised and defended the ultimate anteriority of God’s salvific initiative. All these facts lead to the complex conclusion that there are, indeed, unresolved differences in Schillebeeckx’ theological oeuvre. There are chronological differences (between early and late) and there are thematic differences (between fundamental theology and sacramentology). To find a way out of this situation, the article adopts a salvation history perspective derived from Schillebeeckx’ own work.